DIRECT COMPUTATIONAL METHOD FOR DEFINING LONGITUDINAL STEEL OF RC SQUARE COLUMNS - Tavio Tavio; Puspa Ramadhani (Journal of Civil Engineering, 2010)
This paper presents a study to examine the significance of longitudinal reinforcement on column strength in terms of interaction between axial capacity and bending moment. A new computer programming was developed to accelerate the computational effort. The program can be used to calculate the need of longitudinal reinforcement directly without constructing the P-M interaction diagram for a specific rectangular column with various reinforcement ratios. It can be concluded that longitudinal reinforcement ratio affects the column capacity significantly. The originality of the program is also one of the key points in the development of the program for modern analytical tool. The computational procedures developed in the program were based on ACI 318M-02 and SNI 03-2847-2002. The results have also been proven to be accurate when compared with PCA Col program.